Integrating Sticky Prices and Sticky Information - Dupor, Bill; Kitamura, Tomiyuki; Tsuruga, Takayuki (The Review of Economics and Statistics, 2010)
Understanding the relationship between nominal and real variables, most notably inflation and cyclical output, is one of the fundamental questions of economics. Toward this understanding, we develop a model that integrates sticky prices and sticky information—a dual-stickiness model. We find that both rigidities are present in U.S. data. We also show that the dual-stickiness model's closest competitor is the hybrid New Keynesian model. For both models, current inflation depends in part on last period's inflation. The former model achieves this dependence endogenously through the interaction of the two rigidities rather than through backward-looking behavior. U.S. data support the dual-stickiness model over the hybrid model because lagged expectations terms appear in the former's inflation Euler equation. Finally, we show that it is quantitatively important to distinguish between the two by simulating a dynamic equilibrium model under each of the two inflation equations.